DOI: 10.33540/1055
|View full text |Cite
|
Sign up to set email alerts
|

Hear me out

Abstract: IKR, FVN, and NE designed the studies. IKR performed the data analysis and wrote a first draft of the manuscript. FVN and NE provided substantial comments and suggestions for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
(561 reference statements)
0
0
0
Order By: Relevance
“…We observed that one way of overcoming ingroup bias is to make sure groups have experience with ingroup public good provision before turning to the more complex multigroup public good provision (Chapter 5). Other research shows that newcomers signaling commitment to the group (Choi et al, 2019(Choi et al, , 2021 and signaling good intentions (Rösler, 2022) also help to mitigate ingroup bias. Reducing the salience of ingroup-outgroup divisions in incumbent-newcomer relations may further help to prevent ingroup bias, for example by emphasizing superordinate identities and goals (Gaertner & Dovidio, 2000;Sherif, 1966).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…We observed that one way of overcoming ingroup bias is to make sure groups have experience with ingroup public good provision before turning to the more complex multigroup public good provision (Chapter 5). Other research shows that newcomers signaling commitment to the group (Choi et al, 2019(Choi et al, , 2021 and signaling good intentions (Rösler, 2022) also help to mitigate ingroup bias. Reducing the salience of ingroup-outgroup divisions in incumbent-newcomer relations may further help to prevent ingroup bias, for example by emphasizing superordinate identities and goals (Gaertner & Dovidio, 2000;Sherif, 1966).…”
Section: Limitations and Future Researchmentioning
confidence: 99%